Pengaruh Latihan Aquarobik Terhadap Jumlah Hitung Lekosit Pada Wanita Obesitas Di Kota Semarang - Mukarromah, Siti Baitul; Susanto, Hardhono; Riwanto, Ign.; Rahayu, Tandiyo (Media Ilmu Keolahragaan Indonesia, 2013)
The capacity of physical ability can be improved through doing an exercise which is according to the intensity, duration and frequency. Exercise can improve the immunity system and influence the leucocyte. The number of pheripheral leucocyte can be the resource of information for the diagnostics and prognose the description of organ damage and the recovery after physical training. The purpose of this study to investigate the influence of aquarobic exercises to leucocyte count .This study is experimental with pretest-posttest control group design. The subjects for this study is a women Obese I, 45-50 years old, they were 24 person. The subjects of study were given aquarobic exercises until the reached the targeted heartbeats which is 75% of the maximum heartbeats, duration 60 minutes, 8 weeks aquarobics exercises. The physical activity was done for a moment. Before and after doing the activity, the pheripheral blood was taken to examine leucocyte count. The result of study reveals that there is significantly increasing a value of the average leucocyte count before aquarobic exercises. Based on the result of study, it can be concluded that aquaribics exercises change leucocyte count on Obes I Women.